2000
DOI: 10.1097/00005344-200007000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activation is Increased in Cyclosporin A-Induced Hypertensive Rats

Abstract: One of the most severe side effects of the immunosuppressive agent, cyclosporin A (CsA), is increased risk of thromboembolic complications and drug-related hypertension. Because platelets might be involved in these processes, we tested the possibility of CsA affecting platelet activation, which might contribute to these adverse drug reactions. The experiments were done using Wistar rats, treated or not (control) with CsA (Sandimmun Neoral), 5 and 30 mg/kg/day, for 7 weeks. Systolic, diastolic, and mean blood p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
9
1
Order By: Relevance
“…In our patients, the median pre-dose concentration of CyA was 99 ng/ml. Therefore differences of platelet effects in our study and those of Reis et al [32] and Naik et al [16] could be attributed to differences in the blood concentration of CyA.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…In our patients, the median pre-dose concentration of CyA was 99 ng/ml. Therefore differences of platelet effects in our study and those of Reis et al [32] and Naik et al [16] could be attributed to differences in the blood concentration of CyA.…”
Section: Discussioncontrasting
confidence: 65%
“…Reis et al [32] showed that collagen-induced platelet aggregation was increased in rats treated with CyA. In contrast, the aggregation induced by ADP was not changed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CsA is known to increase platelet activation/aggregation increasing the risk of thromboembolic complications and hypertension (Reis et al, 2000). Significantly higher platelet counts were observed in Neoral  treated rats but not with nCsA or mCsA at any dose; the mean platelet volume (MPV) remained the same across all CsA treatments.…”
Section: Discussionmentioning
confidence: 97%
“…Serotonin is thought to be participating in at least part of this reaction, supporting the results of previous reports in which CsA was assumed to activate serotonin-related platelet activation. 7,9 Although the details of the mechanisms remain to be clarified, Tc as well as CsA may promote thrombotic events in patients treated with BMT.…”
Section: Discussionmentioning
confidence: 99%